Drying shrinkage behaviour of structural lightweight aggregate concrete containing blended oil palm bio-products - Aslam, M.; Shafigh, Payam; Jumaat, Mohd Zamin (Elsevier, 2016)
Oil palm shell (or palm kernel shell) and oil-palm-boiler clinker are two solid wastes from palm oil industry in tropical region. They can be used as aggregate in concrete mixture. Lightweight aggregate concrete with high strength was successfully produced using oil palm shell as coarse lightweight aggregate. However, lightweight concretes containing oil palm shell with normal and high strengths have relatively high drying shrinkage at early and later ages. This study is an effort to reduce drying shrinkage of oil palm shell lightweight concrete. It was found from previous studies that increasing the volume of oil palm shell in concrete increased its drying shrinkage. Therefore, one method to reduce the drying shrinkage is the reduction of oil palm shell volume by substituting this aggregate with another type of aggregate. For this purpose, comprehensive experimental study was carried out to investigate the effect of partial replacement of oil palm shell with oil-palm-boiler clinker aggregate on the shrinkage behaviour of this type of lightweight concrete. Two sets of concrete mixes were designed in this study. In the first set, oil palm shell was replaced with oil-palm-boiler clinker from 0 to 50% with interval of 10% in oil palm shell concrete with a constant water to cement ratio of 0.36. In the second set, the replacement of oil palm shell with oil-palm-boiler clinker was 30–50% with reduced water to cement ratios from 0.36 to 0.295. The influence of curing conditions on drying shrinkage of concretes was also considered. The test results indicated that partially substitutions of oil palm shell with oil-palm-boiler clinker could significantly reduce long term drying shrinkage of concrete. Contribution of oil-palm-boiler clinker in oil palm shell concrete in the range of 30–50% significantly increased the slump of control oil palm shell concrete. Therefore, it was possible to reduce the water content of these concretes to achieve the same workability of the control mix. Reduction on water content further reduced the drying shrinkage of the concrete. Concrete specimens under 7-day moist curing showed higher drying shrinkage compared to air drying condition.